IDEOLOGICAL CHURNING ON INDIAN CULTURE AND CIVILIZATION: ANALYSIS OF DINKAR’S POETRY AND PROSE - Kumar, Priyanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ramdhari Singh ’Dinkar’ has reflected deeply on Indian culture and civilization in his poetry and prose. His work Sanskriti Ke Char Adhyay presents a comprehensive analysis of the cultural and civilizational structure of Indian society. Dinkar clarified the difference between culture and civilization and said that while civilization is a symbol of the material progress of society, culture strengthens moral, spiritual, and social values. He presented the tolerance and coordination of Indian culture as its greatest strength. In this research paper, the ideology on culture and civilization in Dinkar’s literature has been analyzed. An attempt has been made to understand the balance between tradition and modernity, cultural renaissance, and the spirit of nationalism. This study shows that Dinkar’s literature plays an important role in making the society culturally and morally aware. His ideas are relevant even today and can help in solving problems like cultural erosion, inequality, and communalism.